On the Nazeris fauna of Zhejiang, China (Coleoptera, Staphylinidae, Paederinae) - Hu, Jia-Yao; Tu, Yue-Ye; Li, Li-Zhen (Zootaxa, 2016)
Twelve species of Nazeris Fauvel, 1873 are recorded from Zhejiang, China. Three of them are described as new: N. gutianensis Hu & Li, sp. n., N. zhaotiexiongi Hu & Li, sp. n., and N. zhangsujiongi Hu & Li, sp. n. Two synonymies are proposed: N. minor Koch, 1939 = N. nigritulus Hu, Li & Zhao, 2011, syn. n.; N. chinensis Koch, 1939 = N. tianmuensis Hu, Li & Zhao, 2011, syn. n. Nazeris sadanarii Hu & Li, 2010 is newly recorded from Zhejiang.